(untitled) (African Journal of Biomedical Research, 2019)
Mama Decoction® (MD) is an aqueous antimalarial herbal preparation obtained from combination of Mangifera indica, Alstonia boonei, Morinda lucida and Azadirachta indica leaves with each component plant reported to have anti-plasmodial activity. Management of plasmodial infections is usually accompanied by co-administration of antipyretic and analgesic agent with paracetamol being the most common. Therefore, the study investigated the biological implications of co-administration of MD with paracetamol (PA) in in-vivo anti-plasmodial model in mice. The anti-plasmodial activity of MD (1mL/kg bw), chloroquine phosphate (Cq) (10mg/kg bw) alone and co-administration with PA (15mg/kg bw) (PMD and PCq) were evaluated by oral administration using established malaria infection test (Rane’s test). Chloroquine phosphate and distilled water were used as positive and negative controls respectively. Haematological analysis and histopathological evaluation of the liver and kidney were done using standard procedures. Reduction in parasitaemia at day 4 of treatment with MD, PMD, Cq, PCq were 34.80%, 42.36%, 86.84% and 77.25% respectively. PA significantly reduce anti-plasmodial effect of Cq (p=0.0239), while the enhanced activity on MD was not significant (p=0.3090). Significant reduction (p=0.0027) in PCV and Hb in MD, PA and untreated parasitized group were observed. Hepatotoxicity were observed in parasitized treated and non-treated groups with more effect by co-administration with PA. Different levels of renal tubular epithelial necrosis were observed in the parasitized untreated and Cq groups. The results confirmed anti-plasmodial activity of MD, which though non-significantly reduced by its co-administration with paracetamol has hepatotoxic potential